Comportamento alimentar e estado nutricional de portadores do espectro autista: uma revisão integrativa - OLIVEIRA, Fabrícia Leão Cardoso (2023)
Introduction: Individuals with Autistic Spectrum Disorder (ASD) have highly specific dietary requirements, which make them extremely selective, which can affect their nutritional status, making them susceptible to metabolic deficits. Objective: To identify the eating behavior and nutritional status of people with the autism spectrum. Methodology: This research is an integrative literature review of the last ten years, available in databases such as Lilacs, Scielo and Pubmed, using the following keywords: Food; Autistic Spectrum Disorder; Nutrition. Results: 10 articles that met the inclusion criteria were identified, which identified the nutritional status and eating behavior of those involved in the research, through anthropometric parameters, dietary assessments, application of questionnaires on preferences, food frequency and complaints about reported symptoms. of the TGI. Final considerations: People with ASD are more vulnerable to their nutritional status. In view of this, diets that exclude gluten and casein can reduce deleterious effects on the TGI, which is one of the systems most affected by this dynamic. In addition to the deficiency of Vitamin A and Iron, which can also be an aggravating factor. Thus, the monitoring of the professional nutritionist, through inclusion in nutritional education programs and insertion of this understanding in the family environment, can mitigate the harmful effects arising from this process, in addition to improving the dynamization of the eating process.